Determinants of High Titer in Recombinant Porcine Endogenous Retroviruses - Harrison, Ian (American Society for Microbiology, 2004)
Porcine endogenous retroviruses (PERVs) pose a potential stumbling block for therapeutic xenotransplantation, with the greatest threat coming from viruses generated by recombination between members of the PERV subgroup A (PERV-A) and PERV-C families (PERV-A/C recombinants). PERV-A and PERV-B have been shown to infect human cells in culture, albeit with low titers. PERV-C has a more restricted host range and cannot infect human cells. A recombinant PERV-A/C virus (PERV-A14/220) contains the PERV-A sequence between the end of pol and the middle of the SU region in env. The remaining sequence is derived from PERV-C. PERV-A14/220 is approximately 500-fold more infectious than PERV-A. To determine the molecular basis for the increased infectivity of PERV-A14/220, we have made a series of vector constructs. The primary determinant for the enhanced replicative potential of the recombinant virus appeared to be the env gene. Using a series of chimeric env genes, we could identify two determinants of high infectivity; one was an isoleucine to valine substitution at position 140 between variable regions A and B, and the other lies within the proline rich region. Taken together, these results show that the novel juxtaposition of env gene sequences enhanced the infectivity of PERV-A14/220 for human cells, perhaps by stabilization of the envelope glycoprotein or increased receptor binding.